MENGUKUR BULLWHIP EFFECT PRODUK MAS (PADA JARINGAN SUPPLY CHAIN PT.SEMBILAN PILAR UTAMA DAN SWALAYAN KOYA) - Anugrah Putra Jaya; Syamsul Bachri (Management Insight: Jurnal Ilmiah Manajemen, 2017)
The purpose of this study is to measure the bullwhip effect in supply chain MAS 240 ml in PT. Sembilan Pilar Utama and Swalayan Koya. This research measure method is using bullwhip effect method that presented by Fransoo and Wouters (2000). The results of research, we know that the bullwhip effect happened because of the coefficient of variation orders higher than the coefficient of variation in product demand, inaccurate demand prediction, and order batching. The solution that may be effective to reduce the bullwhip effect that occurs is more concerned with the pattern of order and the product demand.Keywords: supply chain management, bullwhip effect.